Microstructure, mechanical properties and heat-resistance properties of bismaleimide composites modified synergistically by alumina and two kinds of thermoplastic resins. (June 2021) - Chen, Yufei; Dong, Lei; Zhao, Hui; Liu, Zhenda; Zhu, Li; Shang, Yuyang
Al2 O3 -PES-SPEEK/MBAE composites has been prepared, polymer matrix (MBAE) was obtained with 4, 4'-diamino diphenyl methane bismaleimide (BMI) as reaction monomer, 3, 3'-diallyl bisphenol A (BBA) and bisphenol A diallyl ether (BBE) as the reactive diluent, and two kinds of thermal plastic resins (polyether sulfone PES and sulfonated poly(ether ether ketone) SPEEK) as the reinforcements, nano-alumina (Al2 O3 ) prepared by Sol–Gel method as the filler. The microstructure of SPEEK, Al2 O3 and the composites were characterized, the mechanical properties and heat resistance of the composites were also studied and analyzed. The results reveal that there are sulfonic acid groups in SPEEK structure and the microstructure is more loose, and the degree of sulfonation is about 41.3%. Al2 O3 is a nano-sized short-fibrous crystal with hydroxyl groups on its surface. The micromorphology of Al2 O3 -PES-SPEEK/MBAE composites show that the proper amount of PES, SPEEK and Al2 O3 are uniformly dispersed in the matrix resin, which improves the fracture surface morphology of the composite, the shape of the section is fish scale and the fracture cracks are irregular and divergent, and the composites are ductile fracture. The mechanical properties indicate that the flexural strength, flexural modulus and impact strength of the composite is the maximum value 172.9 MPa, 4.7 GPa and 21.4 kJ/m 2, which is 73.1%, 74.1% and 125.3%, higher than the matrix resin, respectively, when the PES content is 3 wt%, 2 wt% SPEEK and 3 wt% Al2 O3 in the composite. At this time, the thermal decomposition temperature of the composite material is 453.5°C, which is 15.4°C higher than that of the matrix resin, and the mechanical properties and heat-resistance properties of the Al2 O3 -PES-SPEEK/MBAE composite are significantly improved.